International Migration from Public Health Systems. Case of Romania - Mihai Păunică; Ileana Cosmina Pitulice; Aurelia Ștefănescu (Amfiteatru Economic)
Approaches concerning international migration from public health systems are a constant challenge because of the multidimensional consequences of it. Globalization, the low degree of economic development in Romania (and consequently the sub-development of health system) comparing to other countries, the opportunities offered by foreign health systems, the dynamic of professional, social and innovative motivations of physicians emphasize the migration phenomenon in Romanian health system. Our research includes an interview-based investigation over the opinion of doctors employed in the public health system on international migration. The interview-based research results revealed many shortcomings in the health system, transformed into as many arguments of the decision on international migration. Also, our research shows that relevant institutions do not hold more than an approximate number of doctors who studied in Romania but are currently practicing in the benefit of patients abroad. In this context, conclusions include the need for a reporting framework over the migration of doctors.